Effect of rainfall on matric suctions in a residual soil slope - Rahardjo, Harianto (2011)
A slope stability study involving shallow slip surfaces should include the effect of negative pore-water pressures in a slope. A field instrumentation program was carried out to monitor negative pore-water pressure (i.e., in situ matric suction) in a residual soil slope in Singapore. Variations in matric suction and the matric suction profiles under (1) a canvas-convered grassed surface, (2) a grassed surface, and (3) a bare ground surface, in response to rainfalls were investigated. Changes in matric suction due to changes in climatic conditions decrease rapidly with depth. The change was found to be most significant in the bare slope and least significant under the canvas-covered slope. The amount of decrease in matric suction after a rainstorm was observed to be a function of the initial matric suction just prior to the rainstorm. Positive pore-water pressures were observed above the groundwater table, suggesting the development of a perched water table within the slope. These observations are also typical of other regions experiencing high seasonal rainfalls. The field monitoring program presented can be adopted for investigating rainfall-induced landslides in other parts of the world.